Fiscal Federalism and Sustainable Tourism in Nepal: Strengthening Local Communities in Pokhara Metropolitan City - Poudel, Lok Nath (Academia Journal of Humanities & Social Sciences, 2026)
This paper aims to examine the policy/practice mismatch of the management of tourism revenues of iconic tourism attractions in Pokhara-Phewa Lake, Gupteshwor, and Mahendra Cave under the execution of fiscal federalism in Nepal. Although the Constitution of Nepal requires local sharing of benefits, the gaps in implementation still exist. This study is presented via the mixed-method approach, which incorporates legal examination of the Constitution and Intergovernmental Fiscal Arrangement Act, 2074, surveys, and interviews, which show that the revenue system is disjointed and opaque. The results indicate poor enforcement, little government royalty, and extralegal control, without being able to pay the communities to receive the impacts of tourism and vulnerabilities to climate change. The study suggests a modified policy framework that should focus on the involvement of local communities in the decision-making in tourism. One of the vital suggestions is to ensure an efficient collection of royalty through the revenue sharing policies by earmarking and the statutory requirement of the democratically managed Community Tourism Benefit Fund. The rationale of this framework is to operationalize fiscal federalism, share benefits fairly, empower local communities, and safeguard the natural heritage of Pokhara Metropolitan City that will be compatible with sustainable development.